Strategies to innovate emergency care of status epilepticus - Jaideep Kapur (Neurotherapeutics)
Generalized Convulsive status epilepticus (SE) is a neurological emergency because prolonged convulsions can cause respiratory compromise and neuronal injury. Compromised GABA-mediated inhibition is a defining feature of SE, and many current therapies are benzodiazepines, which are allosteric modulators of GABA-A receptors. Many patients with medically refractory epilepsy are at risk for SE. Newly available nasally delivered benzodiazepines: midazolam and diazepam given for seizure clusters may prevent SE. Although three different benzodiazepines, diazepam, lorazepam and midazolam terminate early SE, midazolam is preferred. It is administered via the intramuscular route, which saves time and is at least as practical or more effective than intravenous lorazepam. Unfortunately, many early SE patients are receiving inadequate doses of benzodiazepines. Patients who fail to respond to adequate doses of benzodiazepines are considered to be in established SE. Levetiracetam, fosphenytoin, and valproic acid are equally safe and effective in treating established SE. The rate of cardiovascular complications: cardiac arrhythmias and hypotension were low in patients treated with phenytoin, levetiracetam, or valproic acid. In contrast, overall, 25 ​% of patients in established SE were intubated, and this was in response to respiratory compromise in many patients. Interestingly, children treated with fosphenytoin were more likely to require intubation than those treated with valproic acid or levetiracetam. Better therapies are needed for the treatment established SE, because all three drugs were effective in less than 50 ​% of the patients.